2014
DOI: 10.5009/gnl.2014.8.3.306
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Pancreatic Stent Placement for Endoscopic Duodenal Ampullectomy: A Single-Center Retrospective Study

Abstract: Background/AimsWe investigated the efficacy of prophylactic pancreatic stent placement for preventing postprocedure pancreatitis in patients undergoing endoscopic papillectomy.MethodsThis retrospective study included 82 consecutive patients who underwent endoscopic papillectomy for benign ampullary neoplasm at Samsung Medical Center between August 2002 and June 2011. The patients were subdivided into two groups, namely, those who received prophylactic pancreatic stent placement and those who did not. Patient d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…Although the usefulness of prophylactic PPS placement has been demonstrated in some studies 4,8,30 , the precise role of PPS placement in preventing AP after EP remains to be determined, and its use has been questioned in recent series that failed to demonstrate a reduction in AP risk 7,11,12 . Chang et al 11 published a retrospective study of 82 patients who underwent EP, with PPS placement in 54 and no stent placement in 28 (patients with patulous MPD opening after EP), reporting an incidence of AP of 10.5% in the stented group vs 7.14% in the unstented group, but with no significant difference between the groups (p = 1.00).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the usefulness of prophylactic PPS placement has been demonstrated in some studies 4,8,30 , the precise role of PPS placement in preventing AP after EP remains to be determined, and its use has been questioned in recent series that failed to demonstrate a reduction in AP risk 7,11,12 . Chang et al 11 published a retrospective study of 82 patients who underwent EP, with PPS placement in 54 and no stent placement in 28 (patients with patulous MPD opening after EP), reporting an incidence of AP of 10.5% in the stented group vs 7.14% in the unstented group, but with no significant difference between the groups (p = 1.00).…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic PPS placement appears to prevent obstruction of the pancreatic flow secondary to edema that is caused in the region by tumor resection using electrocautery. Studies addressing this issue are still scarce, and many of them have produced conflicting results 7,11,12 .…”
mentioning
confidence: 99%
“…45,48,68,75,86 A recent retrospective study of 82 patients, however, suggested that routine pancreatic duct stenting may not be necessary. 89 Others have suggested that pancreatic duct stents should be used only if pancreatic duct drainage is deemed suboptimal or if the pancreatic duct is difficult to cannulate after the procedure. 46,54,69 Pancreatic duct stent placement typically is performed after papillectomy and may be facilitated by wire-guided papillectomy.…”
Section: Electrocautery Settingsmentioning
confidence: 99%
“…4,7,8,60,61 Some investigators showed that the adoption of the prophylactic PS placement after EP did not correlate with the subsequent development of post-procedural pancreatitis. 9,62,63 Although prophylactic PS is moderately recommended during EP by American Society for Gastrointestinal Endoscopy, studies published to date have not reached consistent consensus regarding whether prophylactic PS should be routinely adopted for EP. 64 Recently published a systemic review and meta-analysis 65 reported that prophylactic PS decreased the odds of post-procedure pancreatitis (odds ratio [OR], 0.71; 95% confidence interval [CI], 0.36-1.40; P = 0.325) as well as late papillary stenosis (OR, 0.35; 95% CI, 0.07-1.75; P = 0.200; I 2 = 0%), increased the odds of bleeding (OR, 1.32; 95% CI, 0.50-3.46; P = 0.572; I 2 = 0%), and perforation (OR, 2.25; 95% CI, 0.33-15.50; P = 0.412; I 2 = 0%), but not significantly.…”
Section: Techniquesmentioning
confidence: 99%